Synergistic Effect of Acylpyrazolone Integrated with Multiwalled Carbon Nanotubes on the Electrochemical Analysis of Ascorbic Acid - Mohamad Mahbob, Emi Norzehan; Ahmad, Mohamad Syahrizal; Md Isa, Illyas; Hashim, Norhayati; Ul-Hamid, Anwar; Saidin, Mohamad Idris; Suyanta, Suyanta; Ibrahim, Sofian (Makara Journal of Science, 2024)
Square wave voltammetry, cyclic voltammetry, chronocoulometry, and electrochemical impedance spectroscopy were employed to assess ascorbic acid’s electrochemical behavior in multiwalled carbon nanotubes (MWCNTs)/carbon paste electrode (CPE) modified by 1-phenyl-3-methyl-4-metafluorobenzoyl-5-pyrazolone (HPMmFBP). The ascorbic acid’s irreversible oxidation peak appeared at approximately 0.5 V. The shifting of the peak potential at the pH range of 6.0–8.4 showed the involvement of protons in the ascorbic acid oxidation. Moreover, the shifting of the peak potential with scan rate in the range of 0.07–0.4 V/s confirmed that the oxidation reaction was irreversible. Under optimized conditions, the oxidative peak current showed linear dependence on the ascorbic acid’s concentration between 1 and 1000 μM with limit of detection (LOD) and quantification (LOQ) at 0.1 and 0.34 μM, respectively. HPMmFBP/MWCNT/CPE exhibit good antiinterference ability, reproducibility, repeatability, and stability and was utilized for the accurate and rapid ascorbic acid detection in commercial tablets. Therefore, it has good potential for practical application.